USE OF THE PDCA CYCLE AS A CONTINUOUS IMPROVEMENT PROCESS: example of a case study on ship loading - Dos Santos, Marcelo; Ramalho Reis Filho, Ramilio (Revista Interface Tecnológica, 2021)
The search for permanence in the highly competitive market has made many companies seek to review their work strategies, and link quality to it as a primary factor for growth and prominence. Within this context, the use of the PDCA method can be of great importance so that existing problems are thought about and solved together with ideas and actions that add up to the development of any sector of society. Due to its efficiency and ease of understanding, the PDCA cycle can be applied in every sector. The objective of this study is to highlight the PDCA cycle as a method that brings continuous improvements, pointing out the advantages and disadvantages of the applicability of this cycle. The methodology used was a literature review. The entire research shows the effectiveness of using the PDCA cycle as a method to promote continuous improvement. The articles analyzed bring the application of the cycle in various sectors and in all, the results achieved were satisfactory and determined growth and changes that added quality.
Keywords: Continuous Improvement; Quality; PDCA cycle